Pengembangan Literasi Ekonomi Islam Berbasis Local Wisdom di Pondok Pesantren - Ayif fathurrahman (Cv. Utility Project Solution, 2023)
Community service activities are carried out at Budi Dharma Boarding School Vocational School, Piyungan, Bantul, DIY with the target of students and Islamic boarding schools as institutions that have special advantages in the field of Islamic economic development based on local wisdom with a multicultural approach. The partner problem raised in this community service program is the development of the potential of Islamic boarding schools as the center of the Islamic economic community. Thus community service activities are organized in the form of assistance in the process of increasing understanding of Islamic economics in a comprehensive manner, especially the development of Islamic economic literacy based on local wisdom. This will help partners as an educational institution to develop into Islamic boarding schools based on holistic Islamic economics and can maximize the role of Islamic boarding schools for the economically weak community and also have a positive impact on community trust in Islamic boarding schools for entrepreneurs. After the implementation of this community service, there were several achievements as follows: a) Comprehensive knowledge and understanding of Islamic economics has increased, not only being ethically normative, but more towards practice-implementative; b). The more effective and maximal role of Islamic boarding schools in community empowerment programs by increasing Islamic economic literacy based on local wisdom.